2005
DOI: 10.1021/jp0442549
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Dissociative Electron Transfer to Polychloroacetamides. In-Cage Ion−Dipole Interaction Control through the Dipole Moment and Intramolecular Hydrogen Bond

Abstract: The reductive cleavage of chloro- and polychloroacetamides in N,N-dimethylformamide gives new insights into the nature of the in-cage ion radical cluster formed upon dissociative electron transfer. Within the family of compounds investigated, the electrochemical reduction leads to the successive expulsion of chloride ions. At each stage the electron transfer is concerted with the breaking of the C-Cl bond and acts as the rate-determining step. The reduction further leads to the formation of the corresponding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…[28][29][30][31][32]35,[69][70][71][72][73] This rules out the occurrence of a stepwise mechanism, and tends to indicate the presence rather of a concerted process. The nature of this initial electron transfer will be further investigated below.…”
Section: Voltammetric Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31][32]35,[69][70][71][72][73] This rules out the occurrence of a stepwise mechanism, and tends to indicate the presence rather of a concerted process. The nature of this initial electron transfer will be further investigated below.…”
Section: Voltammetric Behaviourmentioning
confidence: 99%
“…3 shows the LUMOs of compounds 1a-g and the SOMOs of their reduced forms (radical anions or radical/anion pairs). [28][29][30][31][32][33][34]36 For compounds 1a-e, the LUMOs are more located on the S-Cl group with a lower factor on the aryl moiety, indicating that the extra electron is most likely injected directly into the s S-Cl bond leading to or concomitant with its dissociation. The SOMOs corresponding to their reduced forms are also more localized on the S-Cl group (s radical anion or radical/ion pair) and provide thus more support to the injection of the extra electron into the s S-Cl bond.…”
Section: Electrolysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental works have confirmed the reality of such interactions and the applicability of the model. These examples mostly concerned heterogeneous reactions [18] but examples of homogeneous electron transfer have also been found. [19] Thus, this effect can be considered to be at the origin of the D ap values obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides several discussions about concerted and stepwise pathways for dissociative electron transfer, [33][34][35] including the use of the electrochemical transfer coefficient (α) as a tool to detect the transition between both pathways. 36 The electrochemical reduction of several polychloroacetamides was studied by Constentin et al 37 on glassy carbon electrode in dimethylformamide by cyclic voltammetry. The authors found that electrochemical reduction of polychloroacetamides leads to their complete dechlorination in successive and separated steps, each one corresponding to the cleavage of one C-Cl bond in a two electron process.…”
Section: Introductionmentioning
confidence: 99%